HUKUM DAN KEKUASAAN DALAM PERSPEKTIF FILSAFAT HUKUM PANCASILA - Nikson Gans Lalu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The Preamble to the 1945 Constitution is a fundamental norm which contains four main ideas which are none other than Pancasila, so it can be concluded that the Preamble to the 1945 Constitution is Indonesian legal philosophy and its body is its legal theory. It is said that because in the Body of the 1945 Constitution the basis for Indonesia’s positive law is faound. The rule of law means that state power is bound by law. Not always a rule of law is a democratic state. The monarchical government also obeys the law. But democracy that is not a rule of law is not democracy in the true sense. Democracy is the safest way to maintain control over the rule of law. The concept of the rule of law must also be understood as a regulation of the limits of power possessed by state institutions. Therefore, apart from limiting these powers, it must be regulated to the relationship between the separation of powers and the relationship between the branches of power.